REKAYASA RANCANGAN MESIN TEMPA RAMAH LINGKUNGAN GUNA MENINGKATKAN KAPASITAS PRODUKSI PADA KELOMPOK PANDE BESI - Waluyo, Joko; Pratiwi, Yuli; Parwati, Cyrilla Indri (JURNAL GAUNG INFORMATIKA, 2019)
This study purpose to design an environmentally friendly forging machine in the group of "DL" and "PRT" pande besi who are partners in the Village of Palbapang, PandakDistrict, Bantul Regency. So far, the two partners have made agricultural equipment manually by treating raw materials or heated iron forged repeatedly using a hammer according to the desired form of agricultural equipment. For this process, 3 workers are needed, even though the current condition of the two groups of pande besi is the difficulty of finding workers, so that market demand related to agricultural equipment cannot be fulfilled.The research method is carried out after all data and information have been collected by designing an environmentally friendly forging machine with the help of showhare autocad, then looking for materials and tools that will be used to make the design of the forging machine, and making environmentally friendly forging machinesaccording to the specifications obtained . Before being submitted to partners, testing of the number of punches per minute, as well as the noise level. The results that have been achieved in this study are the creation of an environmentally friendly forging machine design with the capacity to forge machetes roughly 5 pieces / hour, as well as a one-time blow to the depressed workpiece depth of 2 to 3 mm with the number of blows produced 200 to 250 punch a minute, with the noisecaused to the forging machine at 60 dBA. From these results there was a 45% reduction in the noise figure from the previous one using a 110.17dBA manual tool to 60 dBA.The capacity of agricultural equipment production in the two partners of the iron court group increased to 2 to 3 times when compared to using human labor, and in the end could improve the welfare of the partner iron-iron group and the iron-iron society in general.